2023
DOI: 10.3390/agronomy13071756
|View full text |Cite
|
Sign up to set email alerts
|

How Are Warm-Season Pastures’ Nutritive Value and Fermentation Characteristics Affected by Open Pasture, Silvopasture, and Sward Herbage Maturity?

Abstract: This study aimed to evaluate the forage mass and nutritional value (NV) of Guinea Massai grass (Megathyrsus maximus × Megathyrsus infestum) in an open pasture (OP) or the silvopastoral system (SPS) at different stages of development (SDs). The experimental design was completely randomized, with five replications. The treatments were distributed in a factorial scheme 2 × 4, corresponding to types of systems (OP and SPS) and four SD (vegetative stage—S1, pre-flowering—S2, full flowering—S3 and maturity after flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…(1) The management and utilization of traditional grasslands [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…(1) The management and utilization of traditional grasslands [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Wu et al [18] investigated the current and future distribution of orchardgrass-suitable areas globally and found that the areas suitable for habitats increased at higher latitudes while decreasing at lower latitudes as greenhouse gas emissions increased. Ferreira et al [19] evaluated the forage mass and nutritional value of Guinea Massai grass in an open pasture or the silvopastoral system at different stages of development. These valuable insights will help balance economic development and ecological conservation goals to ensure the sustainable development of forage species and the stability of the ecosystem.…”
Section: The Management and Utilization Of Traditional Grasslandsmentioning
confidence: 99%
“…The crude protein content in the leaves is considered one of the most important nutritional parameters for animal health and productivity(Sharma et al 2023), as ruminants need at least 70 g kg − 1 of crude protein to maintain the microbial metabolic processes in the rumen. Based on this, in the present study, the crude protein content in the rainy and dry seasons can meet the nutritional requirements for ruminants.Plants generally have higher growth rates during the rainy period in the tropics, due to the greater availability of water and nutrients in the soil(Piao et al 2019), resulting in greater biomass production and, consequently, greater accumulation of brous and support tissues, via increased thickness of cell walls(Ferreira et al 2023). Several abiotic factors (e.g., precipitation, temperature, and soil fertility) also have a direct in uence on the nutritional value of forage(Silva et al 2021).…”
mentioning
confidence: 99%